'And you'll suddenly realise 'I've not washed my hands': medical students', junior doctors' and medical educators' narratives of hygiene behaviours. Issue 3 (22nd March 2018) - Cresswell, Penelope; Monrouxe, Lynn V
Abstract : Objective: Compliance to hygiene behaviours has long been recognised as important in the prevention and control of healthcare associated infections, but medical doctors still display some of the lowest rates of compliance of all healthcare workers. We aim to understand compliance to hygiene behaviours by analysing medical students', junior doctors' and medical educators' narratives of these behaviours to identify their respective attitudes and beliefs around compliance and how these are learnt during training. Such an understanding can inform future interventions to improve compliance targeted to areas of greatest need. Design: A qualitative study, using narrative interviews (nine focus groups and one individual interview). Data were analysed thematically using inductive framework analysis. Setting: Teaching hospitals in the UK. Participants: Convenience sample of 25 participants: third-year medical students in their first clinical year (n=13), junior doctors (n=6) and medical educators (n=6). Results: We identified four main themes: (1) knowledge, (2) constraints, (3) role models/culture and (4) hygiene as an added extra. Knowledge varied across participant groups and appeared to influence behaviours; medical students relied on what they have been told by seniors, while medical educators relied on their own knowledge and experience. There was a strong belief that evidence for the effectiveness of good hygiene behaviours is lacking. Furthermore, medical educators' behaviour appears to strongly influence others. Finally, hygiene was predominately viewed as an added extra rather than an integral part of the process. Conclusions: Awareness of the evidence around good hygiene needs to be improved at all levels. Medical students and junior doctors should be encouraged to consider why they are asked to perform certain hygiene behaviours in order to improve ownership of those behaviours. Medical educators need to recognise their responsibilities as role models for their junior counterparts, thereby understanding their role in developing the culture of hygiene practices within their clinical domains.